Triazine-Modified Color-Responsive Triarylboron/Acridine Fluorescent Probe with Multi-Channel Charge Transfer for Highly Sensitive Fluoride Ion Detection - Lei Tang; Jiaoyun Wang; Yuan Liu (Molecules)
A novel fluoride ion fluorescent probe is designed by introducing the strong electron-withdrawing triazine groups into the triarylboron/acridine conjugation system. The A-D-A′ molecular configuration endows this molecule with multiple charge-transfer channels; upon reaction with F−, the triazine groups act as primary acceptors within the molecule, facilitating charge transfer between the acridine units and the triazine groups. During fluoride ion detection, changes in the triarylboron moiety lead to a significant bathochromic-shift in fluorescence emission from green to yellow. Theoretical calculations attribute this phenomenon to a reduction in the molecular S1 state energy level upon fluorination, resulting in a pronounced visible color change and chromogenic response during detection. Based on fluorescence intensity changes with varying degrees of F− coordination, a detection limit as low as 10−7 M was determined for TB-1DMAc-2TRZ, demonstrating the high sensitivity of this probe.